Optimization of fruit tissue sampling method to quantify calcium, magnesium and potassium contents to predict bitter pit in apples - Do Amarante C.V.T.* (2018)
© 2018 International Society for Horticultural Science. All rights reserved.This study was carried out to identify the best tissue sampling method and mineral attribute to predict bitter pit (BP) occurrence in apple fruit. ‘Catarina’ apples were stored at 0±0.5°C and 95% RH for four months and then separated in lots without and with BP symptoms, which were submitted to Ca, Mg and K analysis (mg kg-1 of fresh weight) in the total fraction (TF) of peel+flesh, and in the TF and soluble fraction (SF) of flesh or peel tissues. For the peel+flesh, a wedge-shaped segment was cut longitudinally from the fruit (with 1 cm wide at the equatorial region), discarding the core tissue. For peel (thickness of 2 mm) or flesh (thickness of 6 mm, under the peel) sampling, the fruits were cut along the equatorial region and only the distal end was used. Fruit without BP showed higher Ca content in the TF of peel+flesh and flesh, as well as lower Mg content in the TF and SF of flesh and lower K content in the TF of peel than fruit with BP. Fruit without BP had lower Mg/Ca, K/Ca and (Mg+K)/Ca ratios in the TF of peel+flesh, in the TF and SF of flesh, and in the SF of peel than fruit with BP. Also, fruit without BP had lower K/Ca and (Mg+K)/Ca ratios in the TF of peel than fruit with BP. The results show that BP occurrence in ‘Catarina’ apples is associated with high Mg/Ca and K/Ca ratios in the fruit. In addition, these ratios assessed in soluble extracts obtained from the peel or flesh, at the distal end of apples, represent a valuable approach to predict the risk of BP. Mineral analysis in soluble extract eliminates the step of acid digestion of fruit tissues, substantially reducing costs and time.